Kritik Terhadap Gerakan Pentakosta Ketiga Berdasarkan Prinsip Teologi Reformed tentang Kesinambungan dan Ketidaksinambungan Karya Roh Kudus - Grace Mariany Toumeluk; Johanis Putratama Kamuri (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This research aims to analyze and critique the Third Pentecostal Movement based on the Reformed theological concepts of continuity and discontinuity of the work of the Holy Spirit. This research was conducted using narrative analysis as an approach to discover and analyze the assumptions behind the narratives presented by supporters of the Third Pentecostal Movement. Through this approach, this research found that there is no continuity between the Third Pentecost and the true Pentecost in the Book of Acts, and even the nature of the Third Pentecost contradicts the nature of the true Pentecost, because this movement ignores objective efforts in the form of strict exegesis of the Bible to understand Pentecost and the various accompanying phenomena. The hope for true spiritual revival must always be accompanied by objective efforts in the form of strict biblical exegesis, which is reflected in apostolic preaching and rigorous doctrinal teaching. Because apostolic preaching and strict doctrinal teaching are the means of grace used by the Holy Spirit to protect the church from the spirit of revivalism and to produce genuine revival.